Genomics of elite sporting performance: what little we know and necessary advances. Issue 9 (30th April 2013) - Pitsiladis, Yannis; Wang, Guan; Wolfarth, Bernd; Scott, Robert; Fuku, Noriyuki; Mikami, Eri; He, Zihong; Fiuza-Luces, Carmen; Eynon, Nir; Lucia, Alejandro
Abstract : Numerous reports of genetic associations with performance-related phenotypes have been published over the past three decades but there has been limited progress in discovering and characterising the genetic contribution to elite/world-class performance, mainly owing to few coordinated research efforts involving major funding initiatives/consortia and the use primarily of the candidate gene analysis approach. It is timely that exercise genomics research has moved into a new era utilising well-phenotyped, large cohorts and genome-wide technologies—approaches that have begun to elucidate the genetic basis of other complex traits/diseases. This review summarises the most recent and significant findings from sports genetics and explores future trends and possibilities.